Impact of lockdown on air quality in India during COVID-19 pandemic - Singh, Ramesh P. (Air Qual Atmos Health, 2020)
First time in India, total lockdown was announced on 22 March 2020 to stop the spread of COVID-19 and the lockdown was extended for 21 days on 24 March 2020 in the first phase. During the total lockdown, most of the sources for poor air quality were stopped in India. In this paper, we present an analysis of air quality (particulate matter-PM(2.5), Air Quality Index, and tropospheric NO(2)) over India using ground and satellite observations. A pronounced decline in PM(2.5) and AQI (Air Quality Index) is observed over Delhi, Mumbai, Hyderabad, Kolkata, and Chennai and also a declining trend was observed in tropospheric NO(2) concentration during the lockdown period in 2020 compared with the same period in the year 2019. During the total lockdown period, the air quality has improved significantly which provides an important information to the cities’ administration to develop rules and regulations on how they can improve air quality.